A Study of Perceived Stress and Its Relation with Health Problem among College Teachers during COVID 19 in Delhi /NCR (International Journal of Innovative Research in Engineering & Management, 2021)
To avoid the growth of COVID-19, universities in Delhi are  stopped in March 2020. Several universities and teachers in  Delhi return in September 2020, and instructors face  significant ambiguity as a result of this unique circumstance.  Ever since the start of the crisis, teachers have had  psychological issues. They had to establish virtual learning  during the lockdown, and so when schools reopen, they have  expressed significant anxiety over the new, unexpected  teaching environment. The purpose of this research is to  assess the manifestations shown by teaching personnel in the  Delhi NCR region during the reopening of schools. To do so,  we gathered a sample of 100 instructors who completed an  online questionnaire that evaluated stress, anxiety, and  sadness using the DASS-21 (depression, anxiety, and stress  scale) in addition to gathering socio-demographic data.  According to the findings, a large majority of teachers had  anxiety, sadness, and stress indicators. Gender, age,  employment reliability, the degree of schooling at which they  teach, and parental status all have an impact on this  symptomatology. We believe that it is critical to protect  teachers' mental health to promote both classroom quality and  patient psychological wellbeing.
Keywords: Anxiety; COVID-19; Depression; Indicators; Virtual Learning